The Argument of Al-Hadith Critics in Proving the Hearing of a Narrator (Rawi) from His Sheikh "A Model Study" - Mashgagba , Abdelrhman Mohammad (Jurnal Studi Al-Qur'an, 2020)
This research aims at studying a significant precise issue of the science of Illal al-hadith, which is to discuss the validity of some narrators who al-hadith critics have differed upon in proving their hearing from their Shiekh. In view of the fact that it was not proven that the narrator has heard al-hadith from his Shiekh or some others have refuted it. To achieve the aim of this study, I followed the incomplete inductive method in collecting the models studied and the reviewed data. Then I used the deductive and the critical approach in analyzing and studying these data to conclude a precise result for the issue of hearing. I devoted a chapter to each model. The most significant results of this study include the following: the fact of proving hearing or refuting it is a matter of judgment according to what evidence the critic has found and has proven. it does not always take on consideration the words of the critic who has proven the issue of hearing against the one who has denied it. The existence of many of the evidence used by al-hadith critics to prove hearing or refuting it, and other results. Keywords: The argument of al-hadith critics, proven hearing, defusing of hearing, evidence